Treatment of Class II malocclusion with bialveolar protrusion by means of unusual extractions and anchorage mini-implant - Jong-Moon Chae (Dental Press Editora, 2012)
INTRODUCTION: Patients with dental Class II bialveolar protrusion are generally treated by extracting the four first premolars or two first and two second premolars, and retracting the anterior teeth. This case report describes the treatment of an adult patient with bialveolar protrusion, a Class II canine and molar relationship, and lip protrusion. METHODS: In this patient, the maxillary right second molar (1.7) had to be extracted due to extensive caries. To create sufficient space to retract the anterior teeth, the maxillary right posterior teeth were distalized with a maxillary posterior mini-implant (1.2~1.3 mm in diameter, 10 mm long), which was placed into the maxillary tuberosity area and allowed an en masse retraction of the maxillary anterior teeth. RESULTS: Overall, mini-implant can provide anchorage to produce a good facial profile even without additional premolar extraction in cases of dental Class II bialveolar protrusion with the hopeless second molar. CONCLUSION: The total treatment period was 42 months and the results were acceptable for 34 months after debonding. INTRODUÇÃO: os pacientes com Classe II e biprotrusão alveolar são, geralmente, tratados com extração de quatro primeiros pré-molares ou dois primeiros e dois segundos pré-molares, e retração dos dentes anteriores. Este relato de caso descreve o tratamento de um paciente adulto com biprotrusão alveolar, relação de caninos e de molares em Classe II e protrusão labial. MÉTODOS: nesse paciente, o segundo molar superior direito precisou ser extraído devido a cáries extensas. Para criar espaço suficiente para retração dos dentes anteriores, os dentes posterossuperiores direitos foram distalizados com um mini-implante posterossuperior (1,2 ~ 1,3mm de diâmetro, 10mm de comprimento), que foi colocado na área da tuberosidade maxilar e permitiu uma retração em massa dos dentes anteriores. RESULTADOS: em geral, mini-implantes podem fornecer ancoragem para produzir um bom perfil facial, mesmo sem extração adicional de molares em casos de Classe II com biprotrusão alveolar. CONCLUSÃO: o período total de tratamento foi de 42 meses e os resultados 34 meses após a remoção do aparelho foram aceitáveis.